Religious commitment, subjective income, and satisfaction towards the functioning of democracy in latin america. A mediation analysis model based on Latinobarómetro (2018)
Religion and politics in Latin America maintain a close relation that, along with a historical background in European colonization, remains in force through both being institutionalized in some political parties or ideologies, and diluted in the societies that make up this region. This paper examines the relation between three variables: religious commitment, subjective income, and satisfaction toward the functioning of Latin American democracies. To do so, we have constructed a hypothetical model based on a mediation analysis of 20,204 surveys that were collected by Latinobarómetro in 2016. The results confirm the existence of an indirect positive effect that is motivated by religious commitment, and mediates between perceived income and being satisfied with democracy in Latin America. In other words, as the respondents recognize that they have a greater subjective income and a greater religious commitment, they will probably manifest greater satisfaction toward the functioning of democracy. Such behavior highlights the referential nature of the religious experience by contributing to the emotional reinforcement of the social context perceived by Latin Americans. © 2018 by the author. Licensee MDPI, Basel, Switzerland.